Evaluation of dose‐dependent treatment effects after mid‐trial dose escalation in biomarker, clinical, and cognitive outcomes for gantenerumab or solanezumab in dominantly inherited Alzheimer's disease. Issue 1 (3rd November 2022) - Wang, Guoqiao; Li, Yan; Xiong, Chengjie; McDade, Eric; Clifford, David B.; Mills, Susan L.; Santacruz, Anna M.; Aschenbrenner, Andrew J.; Hassenstab, Jason; Benzinger, Tammie L.S.; Gordon, Brian A.; Fagan, Anne M.; et al.
Abstract: Introduction: While the Dominantly Inherited Alzheimer Network Trials Unit (DIAN‐TU) was ongoing, external data suggested higher doses were needed to achieve targeted effects; therefore, doses of gantenerumab were increased 5‐fold, and solanezumab was increased 4‐fold. We evaluated to what extent mid‐trial dose increases produced a dose‐dependent treatment effect. Methods: Using generalized linear mixed effects (LME) models, we estimated the annual low‐ and high‐dose treatment effects in clinical, cognitive, and biomarker outcomes. Results: Both gantenerumab and solanezumab demonstrated dose‐dependent treatment effects (significant for gantenerumab, non‐significant for solanezumab) in their respective target amyloid biomarkers (Pittsburgh compound B positron emission tomography standardized uptake value ratio and cerebrospinal fluid amyloid beta 42), with gantenerumab demonstrating additional treatment effects in some downstream biomarkers. No dose‐dependent treatment effects were observed in clinical or cognitive outcomes. Conclusions: Mid‐trial dose escalation can be implemented as a remedy for an insufficient initial dose and can be more cost effective and less burdensome to participants than starting a new trial with higher doses, especially in rare diseases. Highlights: We evaluated the dose‐dependent treatment effect of two different amyloid‐specific immunotherapies. Dose‐dependent treatment effects were observed in some biomarkers. No dose‐dependent treatment effects were observed in clinical/cognitive outcomes, potentially due to the fact that the modified study may not have been powered to detect such treatment effects in symptomatic subjects at a mild stage of disease exposed to high (or maximal) doses of medication for prolonged durations.